Plan de negocios para la creación de una empresa dedicada a la comercialización de jabones artesanales en la ciudad de Santiago de Cali. - Martínez Bernal, Gloria Jimena (Universidad Antonio Nariño, 2025)
This project seeks to develop a business plan to determine the viability of creating a company dedicated to the marketing of handmade soaps in the city of Santiago de Cali, which is responsible both in the environmental and social impact of its activities. To achieve this purpose, a market research was carried out, performing an analysis of the product, the potential client, the competition and the possible suppliers. Likewise, the organizational and legal structure of the company was developed, defining key factors such as the technical study, the economic and financial study, data of great importance when identifying the viability or non-viability of the idea